Social Support, Source Credibility, Social Influence, and Impulsive Purchase Behavior in Social Commerce. Issue 3 (3rd July 2019) - Hu, Xi; Chen, Xiayu; Davison, Robert M.
ABSTRACT: Social commerce (s-commerce)—the use of social media to support electronic commerce—has become pervasive. This paper aims to investigate an important type of consumer behaviour that could generate considerable economic value: impulsive purchase behaviour. Specifically, we focus on the role of peer influence. Social influence theory posits that the process via which peers change a consumer's behaviour can be interpreted along two dimensions: informational and normative. Furthermore, drawing from literature, source credibility and social support are proposed as the antecedent factors of the influencing processes in this context. We surveyed 303 s-commerce participants in Sina Weibo to empirically test the research model. The results indicate that peers' expertise and trustworthiness are significantly related to both types of social influence that could exert an influence on a consumer. Further, consumers' exchange of informational and emotional social support significantly facilitates social influence among them. This study contributes to both the s-commerce and the impulsive purchase literature by revealing the role of peer influence in consumers' impulsive consumption behaviour in the s-commerce setting. The practical implications are also illustrated in the paper.